Processing of dairy raw materials in healthy food products - Chabanova, Oksana; Vikul, Svitlana; Sharakhmatova, Tetyana; Bondar, Sergii; Trubnikova, Anastasiia (Technology audit and production reserves, 2017)
The object of research is whey-based beverages. The most problematic areas are the limited shelf life of beverages and the risk of product stratification during storage. In the course of the study, whey pasteurization regimes are used: 84±2 °C, waiting time 15–20 s, so the shelf life of beverages is limited, since sterilization of whey beverages is impossible due to loss of biologically active substances. To prevent delamination of the beverages during the storage of the formulation, pectin is added and an additional operation – homogenization is introduced. Whey beverages with functional properties for individuals controlling body weight are obtained with improvement of organoleptic characteristics of the product. The resulting beverage is suitable, as a result of the introduction of plant components, to improve the metabolism in the body, block the synthesis of fat in adipose tissue, reduce the absorption of carbohydrates and fats in the digestive tract and remove excess fluid, accelerate the cleavage of fat molecules and transform fat into free energy. This is confirmed by the activation of pancreatic lipase. The activity of pancreatic lipase increases in 3.8...4.0 times in comparison with the control (whey). Components of the whey, as the basis of beverages, have low energy value and high biological value. L-carnitine, α-lipoic acid, stevia, gingerol and bromelain stimulate the breakdown of fats. Cinnamon increases metabolism in the body. This helps to accelerate the breakdown of fat. To increase the nutritional value and biological activity to the beverages, the introduction of fruit and berry juices (lemon, cranberry, orange, pumpkin, yostaberry juice). Biologically active substances of juices show antisclerotic, antistress, tonic, immunostimulating, antioxidant effect. Antisclerotic action of juices is associated with the antioxidant properties of vitamins C, E, β-carotene. Juices reduce the oxidation degree of the most dangerous fraction of lipoproteins, thereby slowing the growth process of atherosclerotic plaques in the vessels. Antistress, tonic, immunostimulating and antioxidant effects of juices are due to the content of polysaccharides, sulfur-containing proteins, minerals, vitamins A, E, C, group B, bioflavonoids. Whey beverages for people who control body weight are not toxic, their frequent consumption does not lead to addiction. Beverages do not contain substances prohibited by the Ministry of Health of Ukraine. Shelf life of beverages is 14 days. Beverages can be made on traditional equipment using traditional technology.